Persepsi Masyarakat Terhadap Layanan Pendidikan Madrasah di Jawa Tengah - Siti Muawanah; Aji Sofanudin; Wahab Wahab; Mulyani Mudis Taruna; A.M. Wibowo; Umi Muzayanah; Nugroho Eko Atmanto; Ahmad Muntakhib (EDUKASI: Jurnal Penelitian Pendidikan Agama dan Keagamaan, 2022)
For some years, people have regarded madrasah as the second-class education, but the perception is getting better now due to some evidences. This article is discussing about people’s perception on madrasah’s education services in Central Java. By using a qualitative approach, the study revealed the important results. First, recently, the trend of the number of madrasah and the students has steadily increased, while the number of (secular) schools and their students has shown a decreasing line.  Second, generally speaking, people’s perception on madrasah’s educational services in Central Java is good in all five dimensions. The highest score is given to assurance dimension while the lowest is given to the reliability. Third, Islamic values, good character, and qualified human resources are the strengths to which attract people to enroll their children to madrasah, while facilities and infrastructures are madrasah’s weaknesses.